2018
DOI: 10.1242/dev.167734
|View full text |Cite
|
Sign up to set email alerts
|

Soma-germ line interactions and a role for muscle in the regulation of C. elegans sperm motility

Abstract: The development of highly differentiated sperm cells that are specialized for navigating to and fusing with an oocyte is essential for sexual reproduction. As a major part of differentiation, sperm undergo extensive post-meiotic maturation en route to the oocyte. This is regulated largely by soma-derived cues. In Caenorhabditis elegans, this process is called sperm activation, and it transforms immotile spermatids into migratory fertilization-competent cells. Here, we show that the negative regulator of sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Our data support a cell autonomous role for proline catabolism in sperm. However, although whole animal RNAi of alh-6 closely phenocopies the alh-6 mutant including reduced spermatid size, germline specific RNAi of alh-6 did not significantly reduce the size of spermatids; perhaps suggesting a partial role for ALH-6 in somatic tissues for spermatid development, which is in line with recent studies in C. elegans describing soma to germline signaling in sperm activation (Chavez, Snow, Smith, & Stanfield). Intriguingly, the impact of loss of alh-6 is mostly independent of diet source, unlike the somatic phenotypes which are diet-dependent (Pang & Curran).…”
Section: Discussionsupporting
confidence: 83%
“…Our data support a cell autonomous role for proline catabolism in sperm. However, although whole animal RNAi of alh-6 closely phenocopies the alh-6 mutant including reduced spermatid size, germline specific RNAi of alh-6 did not significantly reduce the size of spermatids; perhaps suggesting a partial role for ALH-6 in somatic tissues for spermatid development, which is in line with recent studies in C. elegans describing soma to germline signaling in sperm activation (Chavez, Snow, Smith, & Stanfield). Intriguingly, the impact of loss of alh-6 is mostly independent of diet source, unlike the somatic phenotypes which are diet-dependent (Pang & Curran).…”
Section: Discussionsupporting
confidence: 83%
“…Many studies have revealed cross talk between germ cells and somatic cells in the modulation of reproduction and aging, such as the regulation of germ cell division and differentiation by somatic cells, and modulation of organismal longevity, stress resistance, and trans-generational inheritance of survival advantages through germ cells [6, 38, 8588]. We found that reproduction blocks future gamete production by signals from smooth muscles, revealing a somatic cell-mediated mechanism in negative feedback control of reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the sperm genes could also be expressed and targeted by sRNAs in somatic tissues. The link between these tissues and its role in spermatogenesis (Chavez et al, 2018) will be intriguing to explore in the future.…”
Section: An Extensive Network Of Spermatogenesis Srna Pathwaysmentioning
confidence: 99%